SAFE RECYCLING OF SPENT MANGANESE DIOXIDE-ZINC VOLTAIC CELLS - Dmitrikov, V. P.; Gorb, O. O.; Boiko, S. I.; Yermakov, V. N. (Scientific Progress & Innovations, 2020)
Ecological aspects, connected with run-down manganese dioxide-zinc voltaic cells and their impact on the environment, are considered. General scheme of methodological approach to recycling galvanic cells scraps is proposed, including the using of information technologies with the substantiation of choosing the recycling method and analytical techniques, converting process, selecting the utilization method of the components and their subsequent selling. Non-waste scheme of technological recycling manganese dioxide-zinc voltaic cells’ scraps has been developed, which successively includes their hydro-mechanical and hydrochemical recycling following the principles of saving resources and energy. During stage-by-stage recycling of manganese dioxide-zinc voltaic cells’ scraps, well-known technological methods and available hardware are applied, which are used in chemical technology and operating on the basis of hydro-mechanical and hydro- chemical processes. At all stages of recycling scraps of manganese dioxide-zinc voltaic elements, techno- chemical control is conducted together with processing the obtained data using software. As a result of recycling manganese dioxide-zinc voltaic cells’ scraps according to the proposed technological scheme, graphite, ammonium chlorine zincate, zinc complex, and manganese dioxide are obtained. Safe utilization of manganese dioxide-zinc voltaic elements’ scraps according to the developed hardware and technological scheme assumes the returning of metallic and soft parts to production and consumption spheres. The proposed scheme is non-waste, environmentally safe, following ecological standards for the natural environment of the region. The scheme’s development is an important stage for industrial object design.